Relationship between Frequency of Fast Food and Beverage Consumption and Tonsillitis in Children - Mukhlis Imanto; Roro Rukmi Windi Perdani; Oktadoni Saputra; Diyan Ekawati; Dustin Delano Pranata Sembiring (Indonesian Journal of Global Health Research, 2026)
Tonsillitis is an inflammation of the palatine tonsils commonly affecting children aged 5–15 years. One of the contributing risk factors is the frequent consumption of fast food and fast beverages. This study aimed to analyse the association between fast food and fast beverage consumption and the incidence of tonsillitis among children aged 5–15 years. An observational analytic study with a case–control design was conducted involving 52 respondents, consisting of 26 cases and 26 controls, selected using consecutive sampling. Data were collected from children aged 5–15 years attending the Otorhinolaryngology outpatient clinic at Advent Hospital. Fast food and fast beverage consumption was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), followed by clinical diagnosis by a specialist. The Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) used to assess fast food and fast beverage consumption was tested for validity and reliability prior to data collection. Item validity was confirmed using correlation analysis with significance values < 0.05, while reliability testing demonstrated satisfactory internal consistency, with Cronbach’s alpha coefficients exceeding 0.70, indicating that the instrument was valid and reliable for measuring dietary consumption patterns. Consumption frequency was categorised as frequent (score ≥ median) and infrequent/never (score < median). Data analysis was performed using the Chi-square test. The study subjects consisted of 27 males (51.9%) and 25 females (48.1%). A total of 26 subjects (50.0%) were diagnosed with tonsillitis, while 26 subjects (50.0%) were non-tonsillitis. Frequent fast food consumption was reported in 25 subjects (48.1%), while frequent fast beverage consumption was reported in 23 subjects (44.2%). Fast food consumption more than twice daily showed a highly significant association with tonsillitis (p = 0.000). Similarly, fast beverage consumption was also significantly associated with tonsillitis (p = 0.000). A high frequency of fast food and fast beverage consumption (OR: 23.100 and 14.929, respectively) is significantly associated with the incidence of tonsillitis in children aged 5–15 years. Health education regarding healthy dietary patterns is essential to reduce the risk of tonsillitis in this age group.